Assessing social security: Some useful results - Christoph Borgmann (Albert-Ludwigs-Universität Freiburg, Institut für Finanzwissenschaft, 2001)
This paper presents a dense summary of the most fundamental results on the issue of PAYG Social Security. They are presented in a simple and insightful analytical framework by working from the budget constraint of the household. The results presented in detail are a representation of the Aaron-Theorem, the equivalence of debt and Social Security, and a proof that under certain conditions the burden of Social Security on the current young and all future generations equals the benefit payments to the current old. Finally, I include uncertainty in the analysis and touch on the intergenerational risk-sharing implications of Social Security.
Keywords: H55; 330; Sozialversicherung; Umlageverfahren; Sozialversicherungsbeitrag; Konsumtheorie; Verschuldungsrestriktion; Overlapping Generations; Öffentliche Schulden; Intergenerative Belastungsrechnung; Theorie